Pandangan Mahasiswa Angkatan 2013/3014 Dalam Menempuh Jenjang Perkuliahan(Studi Kasus Di Progam Studi Pendidikan Biologi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta) - RAHMAT, Rivky Arifarif; , Dr. Sumardi, M.Si; , Dra. Hariyatmi, M.Si (2015)
Rivky Arif Rahmat. Q100120092. The Student's 2013/2014th View in Gradually of Collage (A Case Study in Biology Education Progam, Faculty of Teacher Training and Educational Sciences, Muhammadiyah University Of Surakarta). Thesis. Administration Education. Graduate School. Muhammadiyah University Of Surakarta. 2015. The purpose of the research is generally describe the student's 2013/3014th view in gradually of collage. In detail the purpose of research, that is: (1) describe the source of the information obtained, (2) describe the factors into consideration, and (3) describe the student's 2013/214th hope at the Muhammadiyah University of Surakarta and Biology Education Progam. This type of research based on qualitative approaches, with a case studies research design. The location of this research is in Biology Education Progam. Speaker: student 2013/2014th in Biology Education Progam. The technique of data collection conducted by observation, documentation, and interviews. Technique of data analysis with a snowball technique based on deep interviews result. The validity of the data with the triangulation of the data. The results of this research are: (1) the student 2013/2014th acquire information sources collage at Muhammadiyah University of Surakarta on Biology Education Program by browsing the internet, (2) fundamental considerations there are costs, continuing the student 2013/2014th not too considering the great distances from home, available facilities, and the availability of lecturers and employees in Biology Education Program, (3) the student's 2013/2014th expectations after 1 semester there is ease in turn on AC in classrooms, an expansion of the parking of motorcycles, the addition of a trash in area of the campus, and the existence of a scholarship starting from the 1st semester.